Learning Engagement in Online Professional Development Program: Indonesian University Lecturers’ Insights - Apoko, Tri Wintolo; Hendriana, Benny; Handayani, Isnaini; Hanif, Isa Faqihuddin; Fatayan, Arum; Irdalisa, Irdalisa (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
Online professional development (PD) programs have become integral to educators' lifelong learning, offering opportunities for continuous improvement beyond traditional face-to-face training. However, research is scarce addressing the behavioral, emotional, and cognitive dimensions of engagement in online programs tailored for higher education professionals. This study aims to investigate the extent to which online professional development programs contribute to Indonesian university lecturers' behavioral, emotional, and cognitive engagements. This research used a mixed method with a sequential explanatory design. The participants of this study are 555 university lecturers from diverse universities in Indonesia, both private and state universities, who attended an online training for improving basic skills in instructional techniques held by Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, Indonesia. The instruments used were the questionnaire distributed to all the participants and a semi-structured interview for selected participants. Data analysis included a descriptive analysis for quantitative data and a thematic analysis for qualitative data. The study results show that online PD programs can foster decisive behavioral, emotional, and cognitive engagements among Indonesian university lecturers. Qualitatively, it also unveils positive motivations in pedagogical aspects. Thus, it is recommended that online training for lecturers should be the program offered to lecturers in Indonesia to improve their professionalism, mainly in the teaching aspects continually.